Hydraulic-thermal decoupling simulation model for transient operation of natural gas pipeline networks - Chunyu YU; Chunhao YU; Gang LIU; Rui LIU; Fang YANG; Yang QIN; Lili ZUO; Qian CHEN (You-qi chuyun)
ObjectiveThe transient operation simulation technology for natural gas pipeline networks is essential for peak shaving, economical and safe operation, and diagnosing abnormal service conditions. Currently, the primary challenge in transient operation simulation technology for natural gas pipeline networks is the complexity of the nonlinear coupling of spatial and temporal variables, making it urgent to enhance the calculation efficiency of the simulation process. MethodsIn this study, a hydraulic-thermal decoupling simulation model was established for the transient operation of natural gas pipeline networks. Initially, hydraulic and thermal simulation sub-models were developed based on the coupling relationships between hydraulic and thermal variables in the pipe flow control equation. A time recurrence method was utilized to simulate the entire transient time domain. For each time step, the initial temperature profile of the pipeline network served as the iterative initial value for calculating the temperature at the moment to be solved. The hydraulic sub-model was solved to derive the pressure, density, and mass flow profiles, which were then used as known conditions for the thermal sub-model. Subsequently, the thermal sub-model calculated the temperature and enthalpy profiles. The decision to exit the current time step solution was based on whether the deviation in temperature profile before and after iteration met the specified accuracy requirements. If the accuracy requirements were met, the simulation for that time step concluded; otherwise, the temperature profile from the thermal sub-model was used as the known condition for the hydraulic sub-model, and the process was repeated. Ultimately, through time recurrence, solutions for all subsequent time steps were progressively obtained, detailing the evolution of hydraulic-thermal operating parameters across the entire space-time domain. Results(1) The study comprehensively analyzed the impact of space-time grid step division on calculation speed and accuracy. For spatial steps of 2.5 km, 5.0 km, and 10.0 km, time steps of 30 s and 60 s were selected. The results indicated that the 5.0 km-30 s combination effectively balanced calculation accuracy and efficiency for the decoupling model. (2) When the space-time step sizes were held constant, the decoupling model’s simulation results, based on the coupling model, revealed maximum absolute deviations of 0.003 MPa for pressure and 0.1 K for temperature, while the calculation time was reduced by 42％. This demonstrates the high efficiency of the hydraulic-thermal decoupling model. (3) The decoupling model exhibited strong adaptability across multiple sets of boundary conditions. ConclusionThe hydraulic-thermal decoupling simulation model for transient operation of natural gas pipeline networks significantly enhances the calculation efficiency of dynamic simulations. This model can provide crucial theoretical insights and technical support for advancing transient operation simulation technology and exploring intelligent pipeline network regulation mechanisms.